Interplay between EZH2 and G9a regulates CXCL10 gene repression in idiopathic pulmonary fibrosis - Coward, William R.; Brand, Oliver J.; Pasini, Alice; Jenkins, Gisli; Knox, Alan J.; Pang, Linhua (American Thoracic Society, 2017)
Selective repression of the antifibrotic gene CXCL10 contributes to tissue remodelling in idiopathic pulmonary fibrosis (IPF). We have previously reported that histone deacetylation and histone H3 lysine 9 (H3K9) methylation are involved in CXCL10 repression. This study explored the role of H3K27 methylation and the interplay between the two histone lysine methyltransferases, Enhancer of Zest Homolog 2 (EZH2) and G9a, in CXCL10 repression in IPF. By applying chromatin immunoprecipitation (ChIP), Re-ChIP and proximity ligation assays, we demonstrated that, like G9a-mediated H3K9 methylation, EZH2-mediated H3K27me3 was significantly enriched at the CXCL10 promoter in fibroblasts from IPF lungs (F-IPF) compared with fibroblasts from non-fibrotic lungs (F-NL) and that EZH2 and G9a physically interacted with each other. EZH2 knockdown reduced not only EZH2 and H3K27me3 but also G9a and H3K9me3 and G9a knockdown reduced not only G9 and H3K9me3 but also EZH2 and H3K27me3. Depletion and inhibition of EZH2 and G9a also reversed histone deacetylation and restored CXCL10 expression in F-IPF. Furthermore, treatment of F-NL with the profibrotic cytokine TGF-β1 increased EZH2, G9a, H3K27me3, H3K9me3 and histone deacetylation at the CXCL10 promoter, similar to that observed in F-IPF, which was correlated with CXCL10 repression and was prevented by EZH2 and G9a knockdown. These findings suggest that a novel and functionally interdependent interplay between EZH2 and G9a regulates histone methylation-mediated epigenetic repression of the antifibrotic CXCL10 gene in IPF. This interdependent interplay may prove to be a target for epigenetic intervention to restore the expression of CXCL10 and other anti-fibrotic genes in IPF.